Experimental investigation of interfacial structures within churn flow using a dual wire-mesh sensor. (July 2015) - Parsi, Mazdak; Vieira, Ronald E.; Torres, Carlos F.; Kesana, Netaji R.; McLaury, Brenton S.; Shirazi, Siamack A.; Schleicher, Eckhard; Hampel, Uwe
Highlights: Void fraction data of churn flow were studied using wire-mesh sensor. Different interfacial structures and phase distributions within churn flow were recognized. Velocity and appearance frequency of huge waves were obtained. Abstract: A challenging area in the field of multiphase flow is the study of churn flow. According to the multiphase flow community, churn flow has not been widely investigated in intermediate and large diameter pipes at high gas and liquid flow rates. The present work deals with an experimental study of upward vertical air–water flow in a 76.2 mm I.D. pipe. Superficial gas velocities ranging from 10 to 38 m/s and four superficial liquid velocities (0.30, 0.46, 0.61 and 0.76 m/s) were employed. The experimental data points are mostly located in churn flow and at the transition between churn and annular flow. A dual 16 × 16 Wire Mesh Sensor (WMS) was used to obtain the temporal/spatial variations of phase distributions over the pipe cross-section at one specific axial location ( L / D  = 236). Sequences of phase distributions, axially sliced images, virtual 3-D images as well as void fraction time-series were used to distinguish between different interfacial structures such as slugs and huge waves. Results showed that huge waves occur with either a continuous gas core with a distinct boundary between two phases or a core with a gas–liquid mixture. Furthermore, velocities and frequencies of interfacial structures were obtained. Results are qualitatively and quantitatively consistent with the previous findings available in literature.